Efektivitas Pembelajaran Kooperatif Jigsaw dalam Meningkatkan Kecerdasan Linguistik Siswa - Dian Novita Siswanti; Muh Daud; Dwi Yan Anugrah (Jurnal Psikologi TALENTA, 2022)
The low level of linguistic intelligence greatly affects the learning process of students. Linguistic intelligence can be improved with the jigsaw cooperative learning model. The purpose of this research is to test the effectiveness of jigsaw cooperative learning in improving students' linguistic intelligence. This study used an experimental method with the Randomized Posttest Only Control Group design. Respondents in this study were obtained by simple random sampling technique as many as 30 class XII SMK students. This study uses a linguistic intelligence scale consisting of 15 items. Data analysis in this study used the independent sample t-test with the help of the R version 3.6.2 program. The results obtained in the experimental group were M = 38.00, SD = 3.90 and in the control group, namely M = 34.46, SD = 2.94, so that the jigsaw cooperative learning model was effective in increasing students' linguistic intelligence (t = 2.79, p = 0.00). This study has implications that the jigsaw cooperative learning model is one of the learning models that can be applied to improve students' intelligence, especially in linguistic intelligence.